Anti-Müllerian hormone does not predict time to pregnancy: results of a prospective cohort study. (3rd August 2017) - Depmann, M.; Broer, S. L.; Eijkemans, M. J. C.; van Rooij, I. A. J.; Scheffer, G. J.; Heimensem, J.; Mol, B. W.; Broekmans, F. J. M.
Abstract: In order to study whether ovarian reserve tests (ORTs) can predict time to ongoing pregnancy, we conducted a prospective cohort study in a cohort of healthy pregnancy planners. A total of 102 pregnancy planners were followed for 1 year, or until ongoing pregnancy occurred, after cessation of contraceptives). A baseline measurement of anti-Müllerian hormone (AMH), follicle-stimulating hormone (FSH) and antral follicle count (AFC) was conducted. At the end of follow-up, a semen analysis was performed and chlamydia antibody titres were assessed. A univariate prediction model demonstrated age and the AFC to be significantly capable of predicting time to pregnancy (hazard ratio 0.92, 95% CI 0.87–0.98, p  = 0.01; 1.04, 95% CI 1.01–1.07, p  = 0.02 respectively). In the multivariate model, however, correcting for female age, we found no predictive effect of AMH, basal FSH or the AFC for time to ongoing pregnancy (hazard ratios 1.43, 95% CI 0.84–2.46, p  = 0.36; 0.96, 95% CI 0.86–1.06, p  = 0.43; 1.03, 95% CI 1.00–1.07, p  = 0.08, respectively). This was confirmed by the low C-statistic. We therefore concluded that baseline AMH, AFC or FSH levels do not predict time to ongoing pregnancy in a cohort of healthy pregnancy planners. These results limit the usability of these ORTs in the assessment of current fertility.